Pengembangan Automotive-Hub Platform Ekosistem Otomotif Menggunakan Metode Agile - Saut Pintubipar Saragih; Erlin Elisa; Muhammat Rasid Ridho (TIN: Terapan Informatika Nusantara, 2026)
Current automotive business processes in Batam, encompassing both sales and rentals, remain dominated by conventional methods and the fragmented dissemination of information across social media platforms. This reliance leads to search time inefficiencies, restricted consumer access to specific information, and a distinct lack of an integrated information system capable of accommodating all entities within the automotive business ecosystem. This study aims to bridge this gap by developing an Integrated Automotive-Hub Platform designed to seamlessly and inclusively connect the automotive ecosystem—specifically, industry entrepreneurs and consumers. The software development lifecycle implements the Agile methodology through iterative cycles (Sprints), comprising product backlog creation, iterative development, and continuous testing. Built on a Model-View-Controller (MVC) architecture, the platform features robust core functionalities, including Create, Read, Update, and Delete (CRUD) product management, Peer-to-Peer (P2P) Live Messaging, a Wishlist system, and a Rating & Review module. System evaluation was conducted using Black-Box Testing to validate software functionality, alongside comparative operational time testing to measure the productivity of the new system against traditional manual processes (which utilize messaging applications and spreadsheets). Functional testing results indicate that 14 system scenarios executed perfectly, with no interface or database errors detected. Furthermore, comparative time analyses demonstrate that the platform drastically reduces operational durations within the search and fleet management modules, achieving a Task Success Rate of 95% to 100%. The primary contribution of this research is the engineering of a centralized, public-facing digital automotive ecosystem. This platform tangibly optimizes information transparency (inclusive information), accelerates transaction processes, and minimizes human error within Batam's automotive industry.